Мозаика из дерева - Меликсетян Александр Сергеевич (Просвещение, 1969)
Экземпляры: ИСК (20111012) / Инвентарный номер: 467103 / Цена: 0.44 / Сис.шифр: 85.12 / Авт.знак: М 47 / ГРНТИ: 18 / ББК: 85.125.5